2008
DOI: 10.1371/journal.pone.0002455
|View full text |Cite|
|
Sign up to set email alerts
|

PINK1 Is Necessary for Long Term Survival and Mitochondrial Function in Human Dopaminergic Neurons

Abstract: Parkinson's disease (PD) is a common age-related neurodegenerative disease and it is critical to develop models which recapitulate the pathogenic process including the effect of the ageing process. Although the pathogenesis of sporadic PD is unknown, the identification of the mendelian genetic factor PINK1 has provided new mechanistic insights. In order to investigate the role of PINK1 in Parkinson's disease, we studied PINK1 loss of function in human and primary mouse neurons. Using RNAi, we created stable PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
225
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(246 citation statements)
references
References 63 publications
21
225
0
Order By: Relevance
“…Also, silencing of PINK1 increased susceptibility to MPP+ or rotenone [248]. In this context, decreased expression of PINK1 in human dopaminergic neurons led to reduced longͲterm survival, along with morphological / structural mitochondrial abnormalities and higher levels of oxidative stress [249].…”
Section: Ptenǧinduced Putative Kinase 1 (Pink1)mentioning
confidence: 97%
“…Also, silencing of PINK1 increased susceptibility to MPP+ or rotenone [248]. In this context, decreased expression of PINK1 in human dopaminergic neurons led to reduced longͲterm survival, along with morphological / structural mitochondrial abnormalities and higher levels of oxidative stress [249].…”
Section: Ptenǧinduced Putative Kinase 1 (Pink1)mentioning
confidence: 97%
“…[4][5][6][7] We and others have shown that PINK1 acts as a key neuroprotective protein, aimed at preventing mitochondrial dysfunction and apoptotic cell death in response to multiple stress conditions. [8][9][10] This pro-survival activity is exerted through several mechanisms, including phosphorylation of the mitochondrial proteins TRAP1 and Omi/HtrA2, and regulation of mitochondrial calcium buffering. [11][12][13][14] Increasing data now indicate that PINK1 acts upstream of Parkin in an evolutionary conserved pathway implicated in regulating mitochondrial biogenesis, trafficking and fusion/ fission events, to maintain mitochondrial network health.…”
mentioning
confidence: 99%
“…2,3 The PINK1 gene encodes a serine-threonine kinase with an N-terminal mitochondrial import sequence, first characterized as a protein aimed at maintaining mitochondrial integrity and preventing apoptosis in response to cellular stressors. 2,[4][5][6][7][8] This neuroprotective role is partly exerted through phosphorylation of the mitochondrial chaperon, TRAP1, although cytoplasm-restricted PINK1 was also shown to protect against MPTP damage. 9,10 The full-length PINK1 (PINK1-FL) is processed within mitochondria to generate two mature proteins; 4,11 all three isoforms localize both to the mitochondria and cytosol, their relative ratio being regulated by several factors.…”
mentioning
confidence: 99%
“…[10][11][12][13] Increasing data have demonstrated that absence of functional PINK1 induces abnormalities of mitochondrial morphology. 6,14,15 In several studies (mostly in Drosophila), PINK1 was shown to promote fission acting upstream of the Fis1-Drp1 machinery, and the mitochondrial phenotype observed in PINK1 knockout flies or silenced cells was associated to reduced fission. 16,17 Subsequent studies in mammalian cell systems contradicted these results, demonstrating that mutant or silenced PINK1 resulted in increased fragmentation.…”
mentioning
confidence: 99%